2023
DOI: 10.1002/1878-0261.13506
|View full text |Cite
|
Sign up to set email alerts
|

Parvimonas micra can translocate from the subgingival sulcus of the human oral cavity to colorectal adenocarcinoma

Kelly Conde‐Pérez,
Elena Buetas,
Pablo Aja‐Macaya
et al.

Abstract: Oral and intestinal samples from a cohort of 93 colorectal cancer (CRC) patients and 30 healthy controls (non‐CRC) were collected for microbiome analysis. Saliva (28 non‐CRC and 94 CRC), feces (30 non‐CRC and 97 CRC), subgingival fluid (20 CRC) and tumor tissue samples (20 CRC) were used for 16S metabarcoding and/or RNA sequencing (RNAseq) approaches. A differential analysis of the abundance, performed with the ANCOM‐BC package, adjusting the p‐values by the Holm‐Bonferroni method, revealed that Parvimonas was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 156 publications
0
11
0
Order By: Relevance
“… 2022 ). Moreover, P. micra was also detected by 16S rRNA gene amplicon sequencing in liver tissue in a patient with liver metastasis, although in this case the authors were unable to isolate the bacterium (Conde-Pérez et al 2023 ). These observations suggest a causal link between invasion of distant places by P. micra and CRC.…”
Section: Ectopic Colonization By Oral Bacteriamentioning
confidence: 98%
See 4 more Smart Citations
“… 2022 ). Moreover, P. micra was also detected by 16S rRNA gene amplicon sequencing in liver tissue in a patient with liver metastasis, although in this case the authors were unable to isolate the bacterium (Conde-Pérez et al 2023 ). These observations suggest a causal link between invasion of distant places by P. micra and CRC.…”
Section: Ectopic Colonization By Oral Bacteriamentioning
confidence: 98%
“…In the past, there have been several studies that have shown an association between ectopic colonization by oral bacteria in the intestinal tract and different intestinal diseases. The most studied phenomenons include IBDs (Atarashi et al 2017 , Dinakaran et al 2019 , Hu et al 2021 ), colorectal cancer (CRC; Castellarin et al 2012 , Flemer et al 2017 , 2018 , Osman et al 2021 , Conde-Pérez et al 2023 ) and childhood undernutrition (Vonaesch et al 2018 , 2022 , Chen et al. 2020 , Collard et al 2022 , Donowitz et al 2022 ).…”
Section: Ectopic Colonization By Oral Bacteriamentioning
confidence: 99%
See 3 more Smart Citations